2022
DOI: 10.1111/apm.13249
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 expression and FGFR‐mutations among Danish patients diagnosed with metastatic urothelial carcinoma: A retrospective and descriptive study

Abstract: Checkpoint inhibitors have changed the treatment landscape of advanced urothelial carcinoma (mUC), and recently, a fibroblast‐growth‐factor‐receptor (FGFR) inhibitor has been introduced. This study aimed at estimating programmed death‐ligand 1 (PD‐L1) expression in primary tumors (PTs) and the PD‐L1 expression concordance between PTs and paired metastases in 100 patients with UC managed in the real‐world setting. Further, the aim was to investigate FGFR1–3 aberrations and the correlation between FGFR1–3 aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For the PD-L1 assay used in this study, we had earlier demonstrated a similar staining behavior as for several established PD-L1 antibodies such as clones E1L3N, SP142, and SP263 [ 26 ]. It is of note that a high variability of PD-L1 data also exists in studies using the same antibodies [ 15 , 29 ]. The quantity of tissue analyzed per patient, section age and difficulties in the distinction of intraepithelial or peri-epithelial PD-L1 positive macrophages from true PD-L1 positive cancer cells might also contribute to the data diversity of PD-L1 IHC in the literature [ 26 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the PD-L1 assay used in this study, we had earlier demonstrated a similar staining behavior as for several established PD-L1 antibodies such as clones E1L3N, SP142, and SP263 [ 26 ]. It is of note that a high variability of PD-L1 data also exists in studies using the same antibodies [ 15 , 29 ]. The quantity of tissue analyzed per patient, section age and difficulties in the distinction of intraepithelial or peri-epithelial PD-L1 positive macrophages from true PD-L1 positive cancer cells might also contribute to the data diversity of PD-L1 IHC in the literature [ 26 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%